On the Question of the Legal Form of Socialist Economic Relations - Dabkus, Romualdas (Problemos, 1968)
The legal form of economic relations arises together with the division of public labour and the necessity of barter. The author points out that the institution of property is the legal expression of economic relations of society. The article treats the peculiarities of the legal form of economic relations under socialism, where the institution of the right of property is still necessary as the form of distribution of products. The level of productive forces does not yet allow to satisfy all the requirements of the society. The two forms of socialist property express socialist economic relations. The essence of the transition to the second phase of communism is characterized not by the merging of the two forms of socialist property into one, but by the dying off of the institution of the right of property and of the legal form of economic relations.